Case Report: Oral Fecal Microbiota Transplantation in a Dog Suffering From Relapsing Chronic Diarrhea—Clinical Outcome and Follow-Up - Cerquetella, Matteo; Marchegiani, Andrea; Rossi, Giacomo; Trabalza-Marinucci, Massimo; Passamonti, Fabrizio; Isidori, Marco; Rueca, Fabrizio (Frontiers in Veterinary Science, 2022)
The present case report describes the effects of orally administered fecal microbiota transplantation (FMT) (frozen capsules) in a dog suffering from relapsing chronic diarrhea, needing a continuous low prednisolone dose to maintain the condition under acceptable control. Through FMT, we aimed at evaluating the possibility of improving the clinical score and/or reducing/suspending steroid administration. During a first period of strict monitoring (21 days), the canine inflammatory bowel disease activity index (CIBDAI) score passed from mild to clinically insignificant disease. Furthermore, two additional gastrointestinal signs that had been reported, bloating and episodes of painful defecation, rapidly improved (bloating) or even resolved (painful defecation). The patient was then followed for 18 months (to the authors' knowledge, the longest follow-up time ever reported in a dog), during which no serious relapses occurred and no increase in prednisolone dose was necessary. No adverse clinical effects were ever reported during monitoring. The present description provides a further experience increasing those already present in the veterinary literature, in which an agreement on how to use FMT has not yet been achieved although strongly needed and recommended.